GENDER DIFFERENCES REGARDING STIGMA TOWARDS MENTAL ILLNESS AMONG MEDICAL STUDENTS OF PESHAWAR - Maryum Abdullah; Mifrah Rauf Sethi; Irfan, Muhammad (Journal of Ayub Medical College Abbottabad, 2021)
Background: Stigma towards mental illness is among the main reasons of higher mental health burden in Pakistan, especially in women. Therefore, this study was planned to explore gender differences regarding stigma towards mental illness among medical students of Peshawar. Methods: A Cross-sectional study was conducted among the students of medical and dental institutions of Peshawar from December 2018 to March 2019. Students were asked to respond to the Community Attitude towards Mental Illness (CAMI) scale consisting of 40 questions with four subscales that assess different attitudes towards mental illness. We also asked two additional questions regarding health-seeking behaviour of the general public. Results: The mean age of the sample (n=1003) was 20.75±1.66 years and majority of the respondents were females (n=581, 57.9%). Female, as compared to male students, exhibited positive attitude on overall CAMI scale and its subscales of benevolence and community mental health ideology; while male students showed positive attitude on authoritarian and social restrictiveness subscales, as compared to female students (p<0.05). Both female and male students recognized lack of awareness (combined 34.5%), and stigma attached to mental illness (combined 24.3%) as the main barriers to health seeking behaviour of general public; and suggested that the people struggling with mental health issues should first approach their parents (combined 37.9%) and a psychiatrist/ psychologist (combined 35.0%). Conclusion: Significantly more female medical students showed less stigma towards mental illnesses. Lack of awareness and stigma associated to mental illnesses are considered as the main barriers to help seeking behaviour of general public. Keywords: Stigma; Mental illness; Medical Students